Cooperative Learning in China's EFL and ESL Settings - Guanghai, Hou (UMA Editorial, 2019)
Research on the efficacy of instructional approaches has been of great interest to researchers, scholars, instructors, and policy and planning makers in foreign language education. Cooperative learning, originated in the United States, is one of the most popular and well-researched instructional approaches among them. Various educational researchers presented different definitions of cooperative learning based on their own researches. No matter which definition one employs in classroom contexts, instructors might struggle with the implementation of this approach. Instructional pedagogies develop as modern information technology evolves. A large number of exploratory and empirical studies on cooperative learning were conducted as newly-emerging technologies placed an important role in classroom settings. This dissertation reviewed and analysed important contributions to the evolution of cooperative learning made by researchers, educators and foreign language instructors. It also presented the history of English language education in China as well as foreign language education policies and planning in China since the world-known “reform and opening up”. This research aimed to assist researchers, instructors, and planning and policy makers in foreign language education, to view the importance and efficacy of placing emphasis on instructional approaches - especially the cooperative learning though it evolves from an approach to a strategy used in China’s EFL and ESL settings. This dissertation consisted of six parts, including the framework of the research, the state of the art, the research hypothesis, the methods, the theoretical framework and the evolutions of cooperative learning, and its effects on China’s EFL and ESL reforms.
Fecha de lectura de Tesis Doctoral: 18 de noviembre 2019.
Keywords: Enseñanza - Tesis doctorales; Cooperative learning; Instructional approach; Strategy; Model